2008
DOI: 10.1037/a0013650
|View full text |Cite
|
Sign up to set email alerts
|

Guidance of attention to objects and locations by long-term memory of natural scenes.

Abstract: Four flicker change-detection experiments demonstrate that scene-specific long-term memory guides attention to both behaviorally relevant locations and objects within a familiar scene. Participants performed an initial block of change-detection trials, detecting the addition of an object to a natural scene. After a 30-min delay, participants performed an unanticipated 2nd block of trials. When the same scene occurred in the 2nd block, the change within the scene was (a) identical to the original change, (b) a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 64 publications
(127 reference statements)
3
27
0
Order By: Relevance
“…These findings are consistent with previous research demonstrating that LTM representations can be used to improve change detection performance (Beck et al, 2007;Becker & Rasmussen, 2008;Hollingworth, 2005;Hollingworth & Henderson, 2002;Hollingworth, Williams, & Henderson, 2001;Ryan & Cohen, 2004). Hollingworth (2005) demonstrated that accurate change detection was possible even after a 24-hour delay between the pre-and post-change images.…”
Section: Discussionsupporting
confidence: 81%
“…These findings are consistent with previous research demonstrating that LTM representations can be used to improve change detection performance (Beck et al, 2007;Becker & Rasmussen, 2008;Hollingworth, 2005;Hollingworth & Henderson, 2002;Hollingworth, Williams, & Henderson, 2001;Ryan & Cohen, 2004). Hollingworth (2005) demonstrated that accurate change detection was possible even after a 24-hour delay between the pre-and post-change images.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, the inclusion of pictorial icons in an FOP label may increase the ease with which the information is encoded and remembered 55 . People extract basic meaning from pictures extremely rapidly 56 and form relatively long lasting memory of them 57 , even when people are not actively attempting to form memories of the pictures 58 . These findings suggest that a face might be a particularly effective stimulus for drawing attention to the FOP and conveying relative, qualitative information about the nutritional value of a product.…”
Section: Goals and Objectivesmentioning
confidence: 99%
“…This work has shown that past experience guides what stimuli people perceive as relevant (Becker & Rasmussen, 2008;Summerfield, Lepsien, Gitelman, Mesulam, & Nobre, 2006) and influences how efficiently they select a task to perform (Crump & Logan, 2010;Mayr & Bryck, 2005;Mayr & Kliegl, 2000); both of these findings indicate that memory guides attention and control. Conversely, cognitive control influences memory: Memory tends to be impaired when control demands increase, both when people voluntarily engage in multiple tasks concurrently (Craik, Govoni, Naveh-Benjamin, & Anderson, 1996;Fernandes & Moscovitch, 2000) and when they are distracted by irrelevant stimuli (Wais, Rubens, Boccanfuso, & Gazzaley, 2010).…”
mentioning
confidence: 94%